Human rights violation: Responsibility of international organizations or of their member states - Stojšić Jelena (Međunarodni Problemi)
Although international organizations as subjects of international law are obliged to respect fundamental human rights in their acting, a very small number of them are contracting parties to international instruments for human rights protection, unlike their member states, which are contracting parties to many of them. As international organizations take more and more activities that can and often result in violation of human rights there is an obvious problem to what forum victims of those violations can turn to for determining responsibility of the international organization. The European Court of Human Rights and the European Court of Justice have developed through their practices modalities for indirect control of acts of international organizations by controlling the acts of their member states, which result from their duties as members of those organizations. The paper assumes that such control is efficient and that it fills the void in the international system of determining responsibility for violation of human rights through acts of international organizations according to which, the states basically keep on being responsible for violation of human rights.